6(2x+30)+7(x+1)=u

Simple and best practice solution for 6(2x+30)+7(x+1)=u equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 6(2x+30)+7(x+1)=u equation:


Simplifying
6(2x + 30) + 7(x + 1) = u

Reorder the terms:
6(30 + 2x) + 7(x + 1) = u
(30 * 6 + 2x * 6) + 7(x + 1) = u
(180 + 12x) + 7(x + 1) = u

Reorder the terms:
180 + 12x + 7(1 + x) = u
180 + 12x + (1 * 7 + x * 7) = u
180 + 12x + (7 + 7x) = u

Reorder the terms:
180 + 7 + 12x + 7x = u

Combine like terms: 180 + 7 = 187
187 + 12x + 7x = u

Combine like terms: 12x + 7x = 19x
187 + 19x = u

Solving
187 + 19x = u

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '-187' to each side of the equation.
187 + -187 + 19x = -187 + u

Combine like terms: 187 + -187 = 0
0 + 19x = -187 + u
19x = -187 + u

Divide each side by '19'.
x = -9.842105263 + 0.05263157895u

Simplifying
x = -9.842105263 + 0.05263157895u

See similar equations:

| 10+(a+b)= | | -0.11(13x)= | | (2*7x)+(14+2x)*15=606 | | 3(8x+31)+5(x+1)=u | | 2x+7=X+1 | | 2*7x+14+2x*15=606 | | 2x+14+2x*15=606 | | -10(x-2)= | | 6=9x-8x+3 | | -9x-6y+3= | | 18p-3+7p+31= | | (13+a)+13= | | 0.80x+0.55(80)=0.40(100) | | y-12y= | | 12=m+2 | | 5(6x+35)+7(x+1)=u | | -2y+10=-2(2y+3) | | x-4=-13 | | 16x^2+y^2-16y=0 | | r+10=15 | | 16x^2+y^2=16y | | -2+x=26 | | 2.1=x-6.1 | | (12)(6)6=x | | 3p=18 | | -10x=70 | | -7x=-168 | | -10.1x=30.3 | | 100(84)=96x | | -10x-20=-190 | | 4x+10x=56 | | 12z=-8 |

Equations solver categories